Effect of Plasma Processing and Organosilane Modifications of Polyethylene on Aeromonas hydrophila Biofilm Formation. (30th January 2014) - Kregiel, Dorota; Niedzielska, Kamila
Abstract : The aim of our research was to study how the modifications of polyethylene—a material commonly used in medicine and water industry—influence bacterial cell attachment and biofilm formation. The native surface was activated and modified using two-step process consisting in the activation of native surface with a H2 O vapor plasma followed by its treatment with various organosilanes, namely, [3(tertbutylamine-2hydroxy) propyloxypropyl] diethoxymethylsilane, 1H, 1H, 2H, 2H-perfluorooctylmethyldimethoxysilane, dimethoxydimethylsilane, and isobutylmethyldimethoxysilane. The effect of polyethylene modification after chemical treatment was analyzed using surface tension measurement. The adhesive properties of Aeromonas hydrophila LOCK0968 were studied in water with a low concentration of organic compounds, using luminometric and microscopic methods, and the viability of the adhered bacterial cells was evaluated using the colony forming units method. After two-week incubation the chemically modified materials exhibited better antiadhesive and antibacterial characteristics in comparison to the native surface. Among the examined modifying agents, dimethoxydimethylsilane showed the best desired properties.